Perilaku Petani terhadap Program Asuransi Usahatani Padi (Kasus pada Subak Pangkung Jajung, Desa Baler Bale Agung, Kecamatan Negara, Kabupaten Jembrana) - SANJAYA, I PUTU SURYA; SUARDI, I DEWA PUTU OKA; AMBARAWATI, IGAA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p35, 2022)
Farmer Behavior Towards Rice Farming Insurance Program (Case in Subak Pangkung Jajung, Baler Bale Agung Village, Negara District, Jembrana Regency) Subak Pangkung Jajung is a farmer group that participates in the Rice Farming Insurance program to protect farmers from the risk of crop failure that occurs in farming. The purpose of this study was to determine the behavior of farmers towards the AUTP program. This research was conducted from December 2020 to February 2021 in Subak Pangkung Jajung in Baler Bale Agung Village, Negara District, Jembrana Regency. The research sample amounted to 60 farmers with data collection methods through in-depth interviews and structured interviews (questionnaires), then analyzed using qualitative descriptive methods. The results showed that the behavior of farmers who took part in the AUTP Program was quite good. The behavior of the farmers is formed on the condition of the behavioral components, namely the general knowledge of farmers about the AUTP program is high, farmers both have a very agreeable attitude towards the AUTP program, and the implementation of the AUTP program by farmers who follow the program is classified as good. Subak Pangkung Jajung farmers need to carry out persuasive counseling on the AUTP program to farmers who have not participated in the program, so that their knowledge and attitudes that are classified as good can continue to be real actions following the program. Provisions for claims from the AUTP Program related to the level of damage to farming businesses that receive compensation need to be reviewed. Where the damage rate of 75% is considered too high, so that farmers participating in the AUTP program are difficult to obtain compensation.